Effect of Nano-CaCO3 and Talc on Property and Weathering Performance of PP Composites - Danbee Lee; Seungkyun Kim; Birm-June Kim; Sang-Jin Chun; Sun-Young Lee; Qinglin Wu (International Journal of Polymer Science)
Wood plastic composites (WPCs) are increasingly being utilized these days due to their excellent mechanical properties and low maintenance cost. Despite these advantages, poor UV resistance and low impact strength are drawbacks. To overcome these shortcomings, coextrusion technology has recently been applied in the production of WPCs and it has been showing good results. However, further research on the combination of different functional enhancements is still needed. This study, therefore, manufactured polypropylene (PP) composites filled with UV stabilizer and inorganic fillers (i.e., nano-CaCO3 and talc) and then investigated the influence of weathering on the mechanical and morphological properties of the filled composites as a function of filler type and content. UV stabilizer effectively protected the filled composites from UV-induced photodegradation. At 2.5 wt% nano-CaCO3 (NCC), the NCC particles were well dispersed in the PP matrix, thereby improving the mechanical properties of the filled composites. The best results were observed in 2.5 wt% NCC and 10 wt% talc hybrid filled composites. The composites prepared by adding UV stabilizer to the PP matrix together with NCC and talc exhibited high mechanical properties and improved weathering resistance, and, thus, the combination of NCC, talc, and UV stabilizer in the PP matrix is applicable for shell layer to be used in coextruded WPCs.